INFLUENCE OF SMALL SIDE GAMES (SSG) ON AEROBIC ENDURANCE AND HANDBALL SKILLS - pratama, fitra agung; Yudiana, Yunyun; Juliantine, Tite (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the effect and difference between small side games (SSG) and small side games with tournament (SSGT) on aerobic endurance (endurance) and skills in playing football. The method used in this research is a quasi experimental design with the random pretest-posttest control group design research design. The instrument used is HTPE (The Handball Tactical Performance) to measure playing skills while the Bronco test is to measure endurance. The results showed that there was no significant increase in the SSG training program on the increase in VO2max, while for the playing performance variable the SSG exercise program showed a significant increase. In the SSGT program there is a significant increase in the increase in VO2max and playing performance in PORDA athletes in Kab. West Bandung. Based on the results of the independent sample t-test, there is no significant difference between the SSG training program and the SSGT training program on playing performance, but there is a significant difference between the SSG training program and the SSGT training program on the increase in VO2max in PORDA athletes in Kab. West Bandung.